Chinese patient with neurofibromatosis-Noonan syndrome caused by novel heterozygous NF1 exons 1-58 deletion: a case report - Zhen Zhang; Xin Chen; Rui Zhou; Huaixiang Yin; Jiali Xu (BMC, 2020)
Abstract Background Neurofibromatosis-Noonan syndrome (NFNS) is a rare autosomal dominant hereditary disease. We present a case of NFNS due to the heterozygous deletion of exons 1-58 of the NF1 gene on chromosome 17 in a 15-month-old boy. Case presentation A 15-month-old boy was admitted for motor and language developmental delay, numerous café-au-lait spots, hypertelorism, left blepharoptosis, pectus excavatum, cryptorchidism, secondary atrial septal defect, and UBOs (undefined bright objects) revealed by cranial MRI T2FLAIR in basal ganglia and cerebellum. Using whole exome sequencing, we identified a de novo heterozygous deletion including exons 1-58 of the NF1 gene. Conclusion Although genetic tests are useful tools for diagnosis of NFNS, NF1, or NS, comprehensive analysis of genetic factors and phenotypes is indispensable in the clinical practice. To the best of our knowledge, this case presents the first Chinese NFNS case due to NF1 defects, and the NF1 exons 1-58 deletion-related phenotype is unlike any other reported case.